ANALISIS PENGENDALIAN KUALITAS PRODUK COVER GM5B MENGGUNAKAN METODE SIX SIGMA DAN FAILURE MODE AND EFFECT ANALYSIS DI PT X - Riyanti, Ririn; Ayudyah Eka Apsari (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Quality control is a crucial step in the production process. to maintain product quality and improve process efficiency. PT X is still experiencing defect problems in the GM5B cover product produced through the injection moulding process. During the period of March–May 2025, the total production of GM5B covers reached 13,397 pieces, with 1,145 defective products, resulting in a defect rate of 8,55%, which exceeds the company standard of 4%. The Six Sigma method was used to examine these issues utilizing the DMAIC (Define, Measure, examine, Improve, and Control) methodology. The Failure Mode and Effect Analysis (FMEA) method was used to identify possible failures based on the sources of defects. Risk Priority Number (RPN). The results of the analysis over a 12-week period showed an average Defects Per Million Opportunities (DPMO) value of 28,534.17 and an average sigma level of 3.42. According to the Pareto diagram study, the most prevalent type of defect was contamination, accounting for 36.07%. The causes of contamination defects were further identified using a fishbone diagram to determine the root causes. Further analysis using FMEA indicated that the short shot defect has the highest RPN rating of 270, indicating that corrective action should be given top priority. Improvement proposals were developed using the 5W+1H approach, and the control stage was implemented to ensure that the improvements could be carried out consistently and sustainably